A survey of suicide risk among university students across three regions in Java, Indonesia - Yunitri, Ninik; Rochmawati, Erna; Susanti, Henny Dwi; Nuraenah, Nuraenah; Rayasari, Fitrian; Chairunnisa, Dea; Salsabila, Sephia; Septiawantari, Rani; Slametiningsih, Slametiningsih (Universitas Airlangga, 2025)
Introduction: Suicide remains a significant global health and social problem, with Indonesia showing a lower suicide rate compared to other Asian countries. However, the underreporting of cases in Indonesia suggests that the incidence rate of suicide is higher than documented. This study aimed to identify the risk of suicide among Indonesian college students. Methods: A cross-sectional study was conducted involving 557 students from three universities across Java Island, recruited using the purposive sampling method. The Beck Scale for Suicide Ideation (BSSI) was used to assess suicide risk. The data was analyzed using descriptive statistics to determine the prevalence of suicide-related outcomes. Additionally, linear regression analysis was conducted to examine the associations between suicide risk, suicidal ideation, suicide planning, and self-control in relation to age, sex, and year of study. Results: The average suicide risk among college students was 4.04 (SD= 6.60; 95%CI = 3.49 – 4.59) out of 38, indicating a generally low risk. However, 34.6% of students experienced the desire to die at least once, and 12.7% had a strong desire to make active suicide attempts. Furthermore, 15.8% of students found suicide an acceptable solution to their problems. Gender was found to be significant predictor of overall suicide risk, ideation and self-control. Conclusions: These findings highlight the need for targeted interventions and support for college students to prevent suicide and promote mental well-being.